The Internalization Effort of Student Scientific Attitude through Inductive Teaching Method in Basic Physics Practical Course, Biology Study Program - PMIPA FKIP UR - Zulhelmi Zulhelmi; Muhammad Nur (Universitas Riau, 2017)
The purpose of this study is to know the internalization improvement of scientific attitude of Biology Education Student - PMIPA FKIP UR through the application of Inductive Teaching Methods in the Basic Physics Practical course. The approach used in this study was a Classroom Action Research (CAR) with cyclic pattern which consists of planning, implementation, observation and reflection. After two time actions, the results of the assessment of the scientific attitude of the students increased from 28.46% to 51.50% in cycle 1 and to 79.96% in cycle 2. In general, the indicator scientific attitude has been quite embedded in students. Assessment of student activity increased from 12.56% to 65.50% in cycle 1 and to 78.06% in cycle 2. This result shows that the learning activity by applying the Inductive Teaching Methods has been understood by the students. Assessment on student performance in the implementation of the lab also increased, from the average of 80.55% in cycle 1 to 81.87% in cycle 2. Based on the results of the analysis, it can be concluded that through the application of inductive Teaching Methods in the Basic Physics Practical course in Biology Education Study Program PMIPA FKIP UR can escalation the internalize scientific attitude of student.